Study of left ventricular diastolic dysfunction in recently diagnosed hypertensives in Central Nepal - Laudari, Shankar; Dhungel, Sachin; KC, Pradip Jung; Prasad, Guru; Bhattacharya, Rabindra; Subramanyam, G (Journal of College of Medical Sciences-Nepal, 2016)
CORRECTION: The conclusion on the PDF of this article was replaced on 17th April 2016. The corrected PDF is now available by clicking on the link below. Background & Objectives: Ectopic Left ventricular diastolic dysfunction is now well established as a cause of left sided heart failure and as a powerful predictor of cardiovascular events. It is attributed mostly to systemic hypertension. The objective of the study was to determine the prevalence of left ventricular diastolic dysfunction in recently diagnosed hypertensives in Nepalese population using echocardiography. Materials & Methods: Two-dimensional echocardiography was performed on 120 newly diagnosed patients of systemic hypertension. Transmitral Doppler indexes of diastolic function, Valsalva maneuver applied to the same mitral inflow pattern, pulsed tissue Doppler of the mitral annulus, deceleration time, isovolumic relaxation time and pulmonary venous flow pattern. Results: The age of the patients in our study ranged from 20 to 84 years with mean age of 50years±14.13 years (standard deviation) and male:female ratio being 1.35:1. Hypertensive patients were highest in age group 45-64 years followed by 25-44 years in both the genders. Majority of the patients had stage 1 hypertension (44.16%) followed by stage 2 HTN in 34.17% and pre-hypertension in 21.67%. The majority of the patients in our study had Grade 1 LVDD (66.67%), 10.83% patients had Grade II LVDD, only 2.50% had non-restrictive Grade III LVDD and none had LVDD-IV. Stage II hypertensives had more LVDD(I+II+III): 39/41-95.12% than stage I hypertensives(39/53-73.58%) and pre-hypertensives (8/26-30.77%). The association between stages of systemic HTN and LVDD was found to be highly statistically significant (p=0.002). Conclusion: Our study showed that left ventricular diastolic dysfunction is a common entity in Nepalese population with systemic hypertension. JCMS Nepal. 2016;12(1):14-18.